Survey of Spinal Cord Stimulation Hardware Currently Available for the Treatment of Chronic Pain in the United States - Clingan, Josephine A.; Patel, Ashish; Maher, Dermot P. (Frontiers in Pain Research, 2020)
Background: The number of spinal cord stimulator (SCS) units sold in the United States (US) for the treatment of chronic pain has increased with a corresponding expansion in the number of different SCS platforms available. Each marketed stimulator has several unique features, indications, and limitations, which distinguish one from the other and makes the selection of appropriate hardware possible for optimal patient care. There are an even greater number of similar and overlapping features between SCS. Measures: We used market analysis techniques to survey the currently available SCS technology. We then reviewed published device specifications and manuals for comparison of features. Outcomes: As of 2020, there are nine commonly used SCS platforms made by four manufacturers including four SCS units from Abbott, three from Boston Scientific, and one each from Medtronic and Nevro. Conclusions: A working understanding of each SCS product's nuances is needed for selecting the most appropriate device with which to manage chronic pain patients. Here we present a brief survey of currently available SCS hardware in the US and the features that make each product unique.